Development of Bounce Wall Training Aids To Practice Passing In Volleyball Athletes - Yussirwan Hasibuan; Imran Akhmad (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2022)
This study aims to develop bouncing wall training aids to train passing athletes. The sample/respondent in this study was for a small group trial of 18 athletes from PBV Bina Putri Medan and PBV Gaperta Putra and for large group trials involving 44 athletes. PBV Mulia, PBV TVRI, and PBV Gaperta Putri. The form that has been made beforehand was validated by 3 experts, 1 volleyball coach, 1 sports expert and 1 expert in media/tools, where the percentage of validity is 80% from sports experts, 100% from volleyball experts and 96% from experts media/tools. The method used is the research and development (R&D) method. The results of the small group test involving 18 volleyball athletes PBV Bina Putri Medan as many as 8 athletes got a percentage value of 91% and PBV Gaperta Putra as many as 10 athletes got a percentage value of 92%. volleyball met the criteria to be continued in the large group trial because the average score percentage was 92%. The results of the large group test on 44 volleyball athletes from PBV Mulia Medan as many as 16 athletes got a percentage score of 92%, PBV TVRI as many as 12 athletes and got a percentage value of 92% and PBV Gaperta Putri as many as 16 athletes and got a percentage value of 90%, this shows that the bouncing wall training aid to train volleyball athletes' passing has met the criteria to be continued in the manufacture of mass products because the percentage of the average value is 92%. These training aids are very necessary to train the ability of volleyball athletes in terms of passing, because it is important in training and matches besides that the exercise is not boring and can help coaches train their athletes and also become input for volleyball coaches throughout Indonesia.